Legal Noncompliance in Indonesia Additional Hajj Quota Allocation - Madalia Faza (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The administration of the Hajj pilgrimage in Indonesia is governed by Law Number 8 of 2019, which mandates fairness, transparency, and prioritization of regular pilgrims in quota management. Specific Background In 2024, Saudi Arabia granted Indonesia an additional Hajj quota intended to address prolonged waiting lists, yet its domestic distribution generated controversy due to allocations favoring special pilgrims. Knowledge Gap Existing studies largely emphasize Hajj diplomacy and service management while insufficiently examining legal compliance in the domestic allocation of additional quotas resulting from bilateral agreements. Aims This study examines the Indonesian government’s noncompliance with Law Number 8 of 2019 in distributing the additional 2024 Hajj quota from an international relations and governance perspective. Results The findings reveal discrepancies between statutory provisions and policy practices, marked by the diversion of additional quotas to special pilgrims, limited transparency in decision-making, and weak accountability mechanisms. Novelty This research integrates national interest theory and good governance principles to connect bilateral diplomacy outcomes with domestic legal adherence in Hajj administration. Implications The study underscores that diplomatic achievements in securing additional Hajj quotas must be accompanied by lawful and transparent domestic implementation to preserve public trust, uphold pilgrims’ rights, and ensure coherent governance within Indonesia’s Hajj administration framework. Highlights: Allocation practices diverged from statutory priority for long-waiting regular pilgrims. Decision-making procedures lacked public transparency and administrative accountability. Diplomatic gains were not consistently aligned with domestic legal obligations. Keywords: Noncompliance, Hajj Quota Distribution, Good Governance